Identity and alignment in central Eurasia - MacFarlane, S (2013)
This article examines the extent to which ethnic and religious identity explains alliance/alignment decisions by states in Central Asia and the Caucasus. It finds that identity variables have little direct explanatory role in accounting for these decisions in this region. Instead, alignment choices appear to be driven largely by the strategic context. However, identity factors do have an impact on how policy-makers interpret their strategic context through the influence of these factors on threat perception.